Kristianitas Inklusif atau Pluralis? Diskusi dengan Edward Schillebeeckx - Sunarko, Adrianus (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2015)
Confronted with the inescapable fact of plurality of religions, Christians are called out as well to reformulate their self understanding contextually. This challenge has been thought up by Edward Schillebeeckx as a task to rediscover Christian self understanding which is more open, undiscriminating to other religions, but in the same breath remains authentic to its colour and identity. On the one hand we might see some similarities of Schillebeeckx’s position with the pluralist theologians, given that revelation is viewed as both highlighting the limitless character of God as its subject and admitting human being’s limited horizon to receive it. On the other hand Schillebeeckx never claimed to have been a follower of pluralistic theory. His criticism of Paul Knitter shows a tendency that the former seems to be closer to those adopting inclusivistic theory. This proclivity is related with his christology that gives a unique place to Jesus Christ as the Son of God and the only saviour. Such position need not be discriminative to other religions in so far as the uniqueness of Jesus Christ is situated concretely in relation to the universal character of his salvation and providing that the grace characteristic of faith is not neglected.